Targeted Treatment of Relapsed or Refractory Follicular Lymphoma: Focus on the Therapeutic Potential of Mosunetuzumab - Lopedote P; Shadman M (Cancer Management and Research, 2023)
Paolo Lopedote,1 Mazyar Shadman2,3 1Department of Medicine, St Elizabeth’s Medical Center, Boston, MA, USA; 2Clinical Research Division, Fred Hutchinson Cancer Center, Seattle, WA, USA; 3Department of Medicine, University of Washington, Seattle, WA, USACorrespondence: Mazyar Shadman, Clinical Research Division, Fred Hutchinson Cancer Center, 1100 Fairview Ave, Seattle, WA, 98109, USA, Tel +1 206-667-5467, Email mshadman@fredhutch.orgAbstract: Follicular lymphoma is the most common indolent non-Hodgkin’s lymphoma, and because of the incurable nature of this disorder, new therapies are constantly needed. The recently approved T-cell-dependent bispecific antibody mosunetuzumab showed promising results and manageable toxicities for patients with relapsed or refractory follicular lymphoma. Namely, as opposed to cellular immunotherapy options, this agent has the potential of being effective in patients with unfavorable features with a tolerable rate and severity of cytokine release syndrome, immune effector cell-associated neurotoxicity, and infectious complications. Given the recent withdrawal from the market of PI3K inhibitors and the practical challenges in utilizing with chimeric antigen receptor T-cells (CAR-T) for some patients, mosunetuzumab represents a “breath of fresh air” for both patients and hemato-oncologists. More data are required to better define the real potential of this molecule, either alone or in combination with other agents, including antibody drug conjugates, immunomodulators, and checkpoint inhibitors. Future studies will also shed light on the efficacy of mosunetuzumab compared with CAR-T, in well-designed registries or ideally in randomized controlled trials.Keywords: mosunetuzumab, follicular lymphoma, T-cell-dependent bispecific, bispecific antibody